An audit exploring the effectiveness and sustainability of a protocol aimed at increased rates of vaginal birth after caesarean section (VBAC). (18th April 2012) - Wilson, PN; Swaminathan, A; McCloud, K; Pierce, SJ; Lewis, R; Brigham, S; McCormack, J
Abstract : Background: VBAC is a controversial topic with obstetricians varying in the degree to which they consider it should be encouraged. At the Countess of Chester Hospital we audited how the introduction of a new protocol and ethos change aimed at encouraging vaginal birth after a single previous caesarean delivery might effect rates of this. Method: The protocol aimed to actively encourage the process of VBAC as a positive choice. Rates of VBAC were then audited 6 months pre-protocol change, 6 months post protocol change, and at 2.5 years post protocol change. Results: 46% of patients in the pre-protocol change group attempted VBAC compared with 59 % (94/159) at 6 months and 60 % (95/159) at 2.5 years. At 2.5 years the breakdown of indications for repeat elective caesarean section was: maternal request 41%, unfavourable cervix for induction of labour 27 %, obstetric indication 19 %, maternal medical indication 13 %. Conclusion: The introduction of a protocol aimed at increasing VBAC rates following a single previous caesarean through positive counseling can be effective and sustained. In our sample, maternal request (without an objective maternal medical or obstetric need) was the most common reason cited for elective repeat caesarean section. Limitations are small sample size pre-protocol change and lack of data concerning the reasons behind maternal request for repeat c section.